Development of Web-Based Thematic Teaching Materials Using Weebly on Theme 8 Sub-theme 1 Class IV SDN 065000 Medan Marelan - Zidni Ulfi Hasanah; Erlinda Simanungkalit; Masta Marselina Sembiring; Dila Handayani (Indonesian Journal of Basic Education, 2023)
This research was conducted with the aim of knowing the feasibility and effectiveness of using Weebly-based web teaching materials on theme 8 sub-themes 1 class IV SDN 065000 Medan Marelan. This research is about research and development, which refers to the ADDIE research and development model. The results of this research and development show that web-based teaching materials using Weebly that have been developed obtain a percentage eligibility from media experts of 75% and are declared "decent", a percentage eligibility from material experts of 85.71% and are declared "very feasible", and a feasibility percentage from education practitioners of 97.3% and are declared "very feasible". The results of personal trials for web teaching materials using Weebly get an average score of 1, which is in the "good" category. The results of the field trial phase showed that the effectiveness criterion achieved with a total of 19 students in the post-test was around 85.71%. Based on these tests, web-based teaching materials using Weebly are declared suitable for use in the teaching and learning process.